De Stichting Restauratie Atelier Limburg. Conservering, restauratie, onderzoek en restauratie-opleiding (Bulletin KNOB, 2000)
The Stichting Restauratie Atelier Limburg (Limburg Conservation Institute) in Maastricht is a provincial conservation studio founded in 1988 in the monastery of Rolduc in Kerkrade. From 1990 onwards, the main activities of the SRAL take place in Maastricht, after 1995 in the Wiebengahal. The SRAL is divided in two departments, the school of conservation and a conservation studio for paintings on panel and canvas, polychrome sculpture, historic interiors and work on paper.The foundation's clients are museums, other public collections and churches. Conservation and research activities performed for non-profit provincial institutions is partly subsidised by the provincial government. The studios in Kerkrade focus on treatments of canvas paintings of large dimensions especially in the context of conservation of historic interiors. The Rijksdienst voor de Monumentenzorg (Netherlands Department for Conservation, RCE) and the Rijksgebouwendienst (Government Buildings Agency) initials most of these projects.Since 1990 SRAL provides for the post graduate ‘Training Programme in Conservation of Paintings and Painted Objects’. Every third year the SRAL selects new students. Candidates have finished a full academic education in art or architectural history or chemistry. The five-year course, divided in a three-year period in Maastricht and two years of internships in three different Dutch museums, focuses on three disciplines: ‘Easel Paintings’, ‘Modern Art’ and ‘Decorated Historic Interiors’.The foundations of the training programme are formed by: object orientated teaching by SRAL staff supported by a vast selection of specialist guest lecturers, a small number of students and direct interchange of ideas and expertise with the Dutch conservation and research community via professional working groups.The three curricula are integrated and are designed to examine and treat the works of art as a whole and in their cultural-historical context. This concept is followed right from the outset of the programme. The Maastricht conservation course is partly subsidised by the Department of Culture from the Ministry of Education, Culture and Science, in collaboration with the Netherlands Institute for Cultural Heritage in Amsterdam.The SRAL actively stimulates the exchange of students and teaching staff. The promotion of knowledge transfer and interdisciplinary discussion on themes concerning historic painting materials, techniques and conservation issues is accomplished through contacts with universities and research projects such as the NWO MOLART project. The international network is reinforced by collaboration with conservation schools abroad.